Classes of convex functions. (15th June 2000) - Rosy, Thomas; Stephen, B. Adolf; Subramanian, K. G.; Silverman, Herb
Abstract : We investigate a family that connects various subclasses of functions convex in the unit disk. We also look at generalized sequences for this family.